Lensing effect on underwater levels of UV radiation - Deckert, Rudolf; Michael, K.J. (Journal of Geophysical Research, 2006)
In the austral spring/summer the Antarctic ozone hole can cause enhanced UVB radiation events in the photic zone of the Southern Ocean. If these events coincide with rich shallow-water algal blooms in the marginal ice zone, a high mortality rate can result. The contribution to the sub-surface radiation field of UVB light flashes created through the focusing of collimated solar radiation by surface waves is sought. A three-dimensional Monte Carlo model with cyclic boundaries was developed to investigate the intensity and temporal characteristics of UVB light flashes. The model accounts for reflection, refraction, absorption and scattering of photons, and is based on a data set of ocean optical properties from 280 to 700 nm. The model includes the effect of biogenic particles and covarying yellow substance. Model runs were performed with collimated light for both 350 and 300 nm. Runs for a flat ocean surface revealed a rapid increase of statistical fluctuations (noise) with depth. This increase was more pronounced at 300 nm. Model runs with sinusoidal surface waves showed significant light flashes which were stronger and penetrated more deeply at 350 nm. At 300 nm, the flashes could exceed the collimated part of surface irradiance for 25% of the time, but were negligible at depths greater than 3.7 m. Small sinusoidal waves produced a more intense focus at a shallower depth than larger sinusoidal waves of the same steepness. Model runs with a more complex ocean surface were less conclusive, as the light flashes were disguised by variations in the water elevation.